Design of TPACK-Based Learning Media in Strengthening Digital Literacy: Penelitian - Yulia Sari Harahap; Teguh Satria Amin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to develop a T-Pack (Technological Pedagogical and Content Knowledge) based learning tool to improve the literacy skills of Al-Washliyah Muslim Nusantara University students. The learning tools are in the form of Lesson Plans (RPP) and Student Worksheets (LKS). Student worksheets are learning media as a means to train students to think, act and behave like young scientists. This research is a development research and is designed using a 4D model development design and the research subjects are 7th semester students of UMN Al-Washliyah. The instruments used are student response questionnaires, observation sheets, literacy ability assessment instruments. Tpack is a learning model that is currently often used in the world of education. The practice of implementing this method includes mastery of technology, pedagogy and knowledge of learning content. Data collection will be carried out to obtain accurate and objective data through observations on the UMN Al-Washliyah campus. The results of the study indicate that the development of TPACK-based learning tools is quite effective in improving literacy skills, with a score of 121, meaning that observers give a good category interpretation with a value of A, while the percentage is 89%.